The Anti-apoptotic Role of 3′-Untranslational Region in Response to Angiotensin II via Mcl1 Expression - Lyu, Dayin; Yan, Hong; Chen, Liyang; Zhang, Lingmin; Du, Yanfeng; Ding, Lexi; Lu, Qiulun (Frontiers in Cell and Developmental Biology, 2021)
Myeloid cell leukemia 1 (Mcl1), an abundant protein in the myocardium, plays an essential role in fibrosis and anti-inflammation in cardiomyocytes to prevent heart failure. However, whether Mcl1 3′-untranslated regions (3′-UTR) has the cardio-protecting function remains unclear. Down-regulation of Mcl1 was observed in adult mice heart tissues after Angiotensin II (Ang II) treatment. Consistent with in vivo results, the reduction of Mcl1 expression was identified in Ang II-treated neonatal cardiomyocytes. Mechanistically, Mcl1 3′-UTR prevented Ang II-induced cardiac apoptosis via up-regulation of Mcl1 and an angiogenic factor with a G-patch domain and a forkhead-associated domain 1 (Aggf1), which plays cardiac-protective role. Our work broadens the scope of gene therapy targets and provides a new insight into gene therapy strategies involving mRNAs’ 3′-UTRs application.